PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KUALITAS KEPUTUSAN MELALUI KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN DENGAN SALING KETERGANTUNGAN SEBAGAI VARIABEL MODERATING - Siti Alliyah (BBM (Buletin Bisnis & Manajemen), 2015)
Management Accounting System (MAS) is a procedure and systems formal that useinformation to maintain and provide an alternative of the various activities the company.Characteristics of accounting information management useful based on managerialperceptions as decision makers are categorized into four properties, namely the scope,timeliness, aggregation, integration. This research aims to test the effect of the use ofinformation technology to the quality of decisions through the characteristics ofmanagement accounting system (SAM) with interdependence as a moderating variable.This research use survey method with sampel is Small and Medium Enterprises (SMEs) inKabupaten Rembang, with cluster sampling obtained sample 138 SMEs. Data werecollected by means of questionnaires directly deliver to the address of the respondents,as well as its own returns the address of the respondents picked according topredetermined promise. Analysis of the data using linear regression. This researchsuggest that information technology influence positive to SAM and SAM influencepositive to decision quality. This is suggest that SAM indirectly can mediate therelationship between information technology with decision quality. Morever, thisresearch also refer that the SAM influence on the quality of decisions is stronger whenmoderated by interdependence.Keyword: information technology, quality of decisions, characteristics of managementaccounting system, interdependence